the role of interferon - gamma( IFN-Y) In infectious mononucleosis like syndrome - AL-Autabbi, Jabbar R.Z. (Journal of the Faculty of Medicine Baghdad, 2007)
Background: infection monomcleosis is caused by the ubiquitous Epstein-Barr virus.